Outcomes of Endoscopic Ultrasound-Guided Biliary Drainage in Patients Undergoing Antithrombotic Therapy - Nozomi Okuno; Kazuo Hara; Nobumasa Mizuno; Shin Haba; Takamichi Kuwahara; Hiroki Koda; Masahiro Tajika; Tsutomu Tanaka; Sachiyo Onishi; Keisaku Yamada; Akira Miyano; Daiki Fumihara; et al. (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The Japan Gastroenterological Endoscopy Society (JGES) has published guidelines for gastroenterological endoscopy in patients undergoing antithrombotic treatment. These guidelines classify endoscopic ultrasound-guided biliary drainage (EUS-BD) as a high-risk procedure. Nevertheless, the bleeding risk of EUS-BD in patients undergoing antithrombotic therapy is uncertain. Therefore, this study aimed to assess the bleeding risk in patients undergoing antithrombotic therapy. Methods This single-center retrospective study included 220 consecutive patients who underwent EUS-BD between January 2013 and December 2018. We managed the withdrawal and continuation of antithrombotic agents according to the JGES guidelines. We compared the bleeding event rates among patients who received and those who did not receive antithrombotic agents. Results A total of 18 patients (8.1%) received antithrombotic agents and 202 patients (91.8%) did not. Three patients experienced bleeding events, with an overall bleeding event rate of 1.3% (3/220): one patient was in the antithrombotic group (5.5%) and two patients were in the non-antithrombotic group (0.9%) (p=0.10). All cases were moderate. The sole thromboembolic event (0.4%) was a cerebral infarction in a patient in the non-antithrombotic group. Conclusions The rate of EUS-BD-related bleeding events was low. Even in patients receiving antithrombotic therapy, the bleeding event rates were not significantly different from those in patients not receiving antithrombotic therapy.